Daniel "more than a prophet"? Images, imagery, imagination, and the mashal in Daniel 2 - Olojede, Funlola (Old Testament essays, 2014)
In Dan 2, King Nebuchadnezzar had commanded his wise men to re-imagine his dream or else he would carry out the unimaginable - a mass execution of all the wise men of Babylon. This article argues that the author of Dan 2 imaginatively employed the mashal in the form of a vision of the night to enable Nebuchadnezzar receive what was meant to be a prophetic message. However, the peshar which was supplied by Daniel was strategically couched in wisdom to accommodate the social context of the narrative. In the light of Daniel's allusion (Dan 2:38) to Nathan's prophetic indictment of David in 2 Sam 12:7, and against Koch's claim that Daniel was more than a prophet because he was a man greatly beloved, it is argued here that Daniel's re-envisioning and interpretation of the king's dream served not just to confirm Daniel as a wise man but to introduce him as a prophet. Thus, the combination of wisdom and prophecy in Daniel is what made him "more than a prophet."